Analisis Penggunaan Energi Listrik Mesin Panen Buah Sawit Tenaga Listrik - Orlando, Corlenius Try; Iswandi, Iswandi; Idris, Muhammad (CV. IRA PUBLISHING, 2025)
This article analyzes the durability of electrical energy in palm fruit cutter machines as an efficient and environmentally friendly innovation in the field of harvesting tools. The machine is designed using a 12V 15A DC motor that converts the rotary motion into translation through a crank slide mechanism, powered by a 35Ah battery. Tests were carried out on oil palm trees 3–5 meters high by monitoring power consumption and operating time. The results show that cutting thick fronds requires 15 Watts/minute, while thin ones require 11.25 Watts/minute. The effective operation duration reaches 1 hour and 52 minutes. Performance factors are influenced by battery condition, cutting load, transmission efficiency, and cutting tool design.